Entropy Product Formula for Gravitational Instanton - Parthapratim Pradhan (Advances in High Energy Physics)
We investigate the entropy product formula for various gravitational instantons. We speculate that due to the mass-independent features of the said instatons they are universal as well as quantized. For isolated Euclidean Schwarzschild black hole, these properties simply fail.